Flavonoids as potential anti-platelet aggregation agents: from biochemistry to health promoting abilities. Issue 29 (17th October 2022) - Sharifi-Rad, Javad; Quispe, Cristina; Shaheen, Shabnum; El Haouari, Mohammed; Azzini, Elena; Butnariu, Monica; Sarac, Ioan; Pentea, Marius; Ramírez-Alarcón, Karina; Martorell, Miquel; Kumar, Manoj; Docea, Anca Oana; et al.
Abstract: Cardiovascular ailments are the number one cause of mortalities throughout the globe with 17.9 million deaths per year. Platelet activation and aggregation play a crucial role in the pathogenesis of arterial diseases, including acute coronary syndrome, acute myocardial infarction, cerebrovascular transient ischemia, unstable angina, among others. Flavonoids-rich plant extracts are gaining interest for treating the heart-related problems due to safe nature of these herbal extracts. Consumption of plant-food-derived bioactives, particularly flavonoids, has shown antithrombotic, and cardiovascular protective effects due to its anti-platelet activity. Preclinical and clinical trials have proven that flavonoid-rich plant extracts are protective against the cardiac ailments through anti-platelet aggregation activity. This review aims to highlight the anti-platelet aggregation potential of flavonoids with a key emphasis on the therapeutic efficacy in humans. The mechanism of flavonoids in preventing and treating cardiovascular diseases is also highlighted based on preclinical and clinical experimental trials. Further studies are the need of time for exploring the exact molecular mechanism of flavonoids as anti-platelet aggregation agents for treating heart-related problems.